Ti3Si0.75Al0.25C2 Nanosheets as Promising Anode Material for Li-Ion Batteries - Jianguang Xu; Qiang Wang; Boman Li; Wei Yao; Meng He (Nanomaterials, 2021)
Herein we report that novel two-dimensional (2D) Ti3Si0.75Al0.25C2 (TSAC) nanosheets, obtained by sonically exfoliating their bulk counterpart in alcohol, performs promising electrochemical activities in a reversible lithiation and delithiation procedure. The as-exfoliated 2D TSAC nanosheets show significantly enhanced lithium-ion uptake capability in comparison with their bulk counterpart, with a high capacity of ≈350 mAh g−1 at 200 mA g−1, high cycling stability and excellent rate performance (150 mAh g−1 after 200 cycles at 8000 mA g−1). The enhanced electrochemical performance of TSAC nanosheets is mainly a result of their fast Li-ion transport, large surface area and small charge transfer resistance. The discovery in this work highlights the uniqueness of a family of 2D layered MAX materials, such as Ti3GeC2, Ti3SnC2 and Ti2SC, which will likely be the promising choices as anode materials for lithium-ion batteries (LIBs).